2016
DOI: 10.1016/j.jds.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Increased cyclooxygenase 2 expression in association with oral lichen planus severity

Abstract: Background/purpose Although some studies have shown induction of cyclooxygenase 2 (COX-2) in oral lichen planus (OLP), an association between COX-2 upregulation and OLP clinical severity has not been investigated. Therefore, we aimed to compare COX-2 expression in OLP with that in normal oral tissues, and to determine correlations between COX-2 expression and both clinical criteria and visual analog scale (VAS) scores. Materials and methods COX-2 expression was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…17 Compared with normal epithelium, COX-2 expression was significantly increased in the oral LP epithelium, which correlated with disease severity. 30 El-Rifaie et al 16 have shown that COX-2 expression in cutaneous LP patients is higher than in normal skin. Our study did not support this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Compared with normal epithelium, COX-2 expression was significantly increased in the oral LP epithelium, which correlated with disease severity. 30 El-Rifaie et al 16 have shown that COX-2 expression in cutaneous LP patients is higher than in normal skin. Our study did not support this.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the COX‐2 gene can be suppressed by anti‐inflammatory cytokines (IL‐4, IL‐10, etc) and glucocorticoids . Compared with normal epithelium, COX‐2 expression was significantly increased in the oral LP epithelium, which correlated with disease severity …”
Section: Discussionmentioning
confidence: 99%
“…With respect to (i) an obvious candidate is COX-2, since this enzyme converts linoleic acid to hydroperoxylinoleates (HPODEs), which are then reduced to HODEs (9). Increased COX-2 activity is a hallmark of OLP (4,5). However, both 9-and 13-HODE are produced by this pathway (9), and so a change in the relative proportions of 9-HODE and 13-HODE would not be expected.…”
Section: Discussionmentioning
confidence: 99%
“…This is, however, in contrast to what has been reported previously by Lysitsa et al who did not find any difference in COX‐2 expression among the various clinical types of OLP. However, Chankong et al found that increased COX‐2 expression was associated with the severity of oral lichen planus.…”
Section: Discussionmentioning
confidence: 99%